ANALISIS KESEHATAN KEUANGAN DAERAH KABUPATEN/ KOTA SE PROVINSI BANTEN TAHUN ANGGARAN 2016-2019 - Achmad Taufik; Eko Sugiyanto; Kumba Digdowiseiso (Ilmu dan Budaya, 2021)
The regional financial condition is an important instrument to assess the extent of the condition of regional financial capacity and performance. In this research, he wants to know the condition of the regional financial health in the regencies / cities in Banten Province, in the period 2016-2019. The research method used is quantitative with the results of calculations described descriptively, the data used is a summary of the realization of the TA budget. 2016-2019, and regional statistical data in numbers, such as total population and gross regional income (PDRB) of each Regency / City in Banten Province. The results of the analysis and findings show that the highest index score in the 2016-2019 period ranged from 0.724 to 0.791, while the lowest index score was between 0.124-0.159. There are 5 regions that show an increase in the index, while 3 other regions have a decrease. In terms of index scores, the regions that experienced an increase in the regional financial health index were Serang Regency (0.162), Lebak Regency (0.138), Serang City (0.084), South Tangerang City (0.023) and Cilegon City (0.003). Meanwhile, the regions whose scores decreased were Tangerang City (-0.009), Pandeglang Regency (-0.035) and Tangerang Regency (- 0.061). In terms of ranking, the highest score index is South Tangerang City and Tangerang Regency. In 2016 the highest score was South Tangerang City (0.724), in 2017-2018 there was a change in ranking, the highest was Tangerang Regency (2017: 0.791) and (2018: 0.742), in 2019 the highest ranking was South Tangerang City (0.747). The districts / cities that did not experience a change in the regional financial health index score rankings were Tangerang City (rank 3), Cilegon City (rank 4) and Serang Regency (rank 5). Meanwhile, the districts with the lowest average index were Lebak (0.244) and Pandeglang (0.147). Meanwhile, based on the type of city government, only Serang City whose score is still below the average index. Meanwhile, in the district government type, Tangerang Regency is the representative of the Regency which has a high index score. Even though Serang City is below average, but in terms of consistent scores, Serang city continues to increase and experience improvement. The regional financial health ranking index score is only compared between districts / cities in Banten Province for the 2016-2019 fiscal year. The development gap and regional fiscal ratio in Banten Province are very visible. The next research, especially to examine the financial performance of the City, can compare with other cities that are considered more equal.